Familial Translocation t(2;4) (q37.3;p16.3), Resulting in a Partial Trisomy of 2q (or 4p) and a Partial Monosomy of 4p (or 2q), Causes Dysplasia - Wang, Jian; Zhou, Shiyuan; He, Fei; Zhang, Xuelian; Lu, Jianqi; Zhang, Jian; Zhang, Feng; Xu, Xiangmin; Yang, Fang; Xiong, Fu (Frontiers in Genetics, 2021)
Background: Wolf-Hirschhorn syndrome, a well-known contiguous microdeletion syndrome, is caused by deletions on chromosome 4p. While the clinical symptoms and the critical region for this disorder have been identified based on genotype-phenotype correlations, duplications in this region have been infrequently reported. Conclusion: Our case report shows that both deletions and duplications of the Wolf-Hirshhorn critical region cause intellectual disability/developmental delay and multiple congenital anomalies.